(3HMK aj GdecGSHs - (3eMeO MSf GHf CHj WGdH GdMSjfj GdbeTgjs
(3ChdgG (B:s
.. (3ceG JQi dCf GdXGgQ Hd GdebWhY Cfg MGRJG dCNP GdeGd YdjgG hef GdeYdhe Cf Med GdeGd aQY KHhJ GdGNJUGU ddJhba Ydi bUO GdGfJaGY GdeYdhe GfJaGFg aj GdebGe hcPG dh SHb (B...s
(3BNQgG (B:s
.. (3HYO JhajQ GdYhV YdjgG jLYdgG JQGHG hYfOg jbhd GdcGaQ jGdjJfj cfJ JQGHG hbGd CHh GdbGSe jLH chf GdYhV OGFeG Ke GSJOdhG Ydi Pdc HhLhg aQGLY gPg eNJUQ ef CMcGe GdCYhGV Ydi bhd GdeYJRdI (B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis